Gender Differences in Interpersonal Behaviors of the Madaris and Public School Teachers in Pakistan - Kaukab, Fauzia; Ali, Rafaqaut (Pakistan Journal of Humanities and Social Sciences, 2023)
The student and teachers' interpersonal behaviours impact the success of ongoing classroom learning tasks. These interpersonal behaviours affect students’ interest in class, self-efficacy, and academic achievements. Gender factors, institutional climate and the institution's social environment echo their teachers' interpersonal behaviours in the classroom. Therefore the current study explored the gender differences in the interpersonal behaviours of the Public school and Madaris teachers in Pakistan. The teachers in Public schools and Madaris in Punjab province were the population of the study. The sample of the study was conveniently selected 555 public school teachers and 421 Madaris teachers. The data was collected by an adapted Urdu version of the Questionnaire on teacher interaction (QTI). Mean results, ANOVA test and Post Hoc test results indicated that Pakistani male teachers in public schools and Madaris have high Admonishing behaviour compared to females. It is recommended that male teachers should reduce their admonishing interpersonal behaviour and understand the importance of interpersonal behaviours in the success of educational endeavours in their institutions.